Lithostratigraphy, microfacies and paleogeography of the shallow marine Middle Limestone Member of the Early Eocene Rusayl Formation, Oman: Relationship to the Early Eocene Climatic Optimum, sea-level changes and regional uplift. (December 2021) - Mattern, Frank; Scharf, Andreas; Al-Sarmi, Musaab; Al-Sayigh, Abdul Razak; Al-Maktoumi, Mohammad; Al-Omairi, Nooh; Al-Rawahi, Taher; Al-Moqbali, Marwan
Abstract: We logged five outcrops of the Middle Limestone Member (MLM) of the Early Eocene Rusayl Formation. The eastern sections contain more, much coarser and also more angular detritus than the western sections. Moreover, notable concentrations of red algae, gastropods, corals, oysters and echinoids only occur in the eastern sections. Benthic foraminifers are typical for the entire MLM, but in the west, they are more abundant (dominated by miliolids). Peloids are restricted to the western sections. While the western sections display a subtidal lagoonal facies, capped by thin intertidal deposits, the coarse clastic material of the eastern sections indicates the proximity of a mountainous paleocoast with a resulting rocky coast environment. The coarse eastern facies proves that the Saih Hatat Dome as part of the Oman Mountains had already emerged while the MLM accumulated. Because of the differences, no outcrop correlations between the western and eastern sections are possible. However, facies boundary correlations among the western sections are feasible, spanning a distance of 23.5 km. Among the eastern sections, basal coarse clastics as well as two bioclastic marker horizons were correlated over 26 km. Deposition of the MLM was favored by high temperatures during the Early Eocene Climatic Optimum (EECO) at 53-51 Ma and a correspondingly high eustatic sea-level. The presence of corals in proximity of a mountainous, rocky paleocoast indicates dry conditions (clear water) during the EECO. The final shallowing-up observed in the west is attributed to the end of the EECO when mean global temperatures and the eustatic sea-level dropped. Shallowing from subtidal to intertidal conditions restricted parts of the lagoon and caused evaporation/hypersaline conditions as indicated by monospecific small miliolids and also by early dolomitization due to Mg-rich brines (reflux model). The western sections show signs of dolomitization. The Al-Khod section is the first one to be reported to be intensely dolomitized. Highlights: The Middle Limestone Member (MLM) displays lagoon (W) and rocky coast (E) facies. The western part is richer in miliolids and other benthic foraminifers. The eastern part is richer in red algae, gastropods corals, echinoids and oysters. Warming caused MLM formation. Cooling caused shallowing-up and the end of the MLM. Clastic influx in the east shows that the Saih Hatat Dome existed at the time.